Breast Carcinoma among Patients Undergoing Breast Diagnostic Ultrasonography in a Tertiary Care Hospital in Nepal - Guragain, Seema; Mandal, Sandip K.; Sharma, Nita; Adhikari, Ganga D.; Richman, Mark; Yadav, Ajay K. (Europasian Journal of Medical Sciences, 2023)
Background Ultrasonography (US) is an important modality for investigating breast lesions, as it lacks radiation exposure, differentiates between solid tumor and fluid-filled cysts, and is particularly-useful for young females with dense breast tissue. This study aimed to determine test characteristics (sensitivity, specificity, positive and negative predictive values, and accuracy), and the prevalence of breast cancer, among patients undergoing diagnostic breast US for clinically-detected abnormalities in a tertiary care cancer hospital in Nepal, comparing US findings with histopathology and cytopathology. Data and Methods A cross-sectional study was conducted among a convenience sample of 418 female patients who underwent diagnostic breast US between April 15 and September 10, 2022. Data were entered and analyzed on SPSS 25.0. Prevalence of cancer was determined among US patients who were referred for tissue diagnosis on the basis of clinical or US findings. Sensitivity, specificity, positive and negative predictive values, and accuracy of US in detecting breast lesions in comparison to histopathology and cytopathology findings were calculated. Results The study respondents’ age ranged from 13 to 75 (±11.8) years. Among 97 patients who underwent fine needle aspiration or biopsy based on US findings, 52 (12.4% of total) were diagnosed with breast carcinoma. The sensitivity, specificity, negative predictive value, positive predictive value, and accuracy of US to detect breast cancer were 94%, 100%, 93.7%, 100%, and 96.9%, respectively. Conclusion Among women with breast complaints or physical examination findings, diagnostic US revealed a high prevalence in the population investigated and demonstrated very good sensitivity, specificity, and accuracy to detect breast cancer. This study confirms the important role of ultrasound in the evaluation of breast lesions, particularly in underdeveloped countries.